Carbon emission tracker and tracking system - LEE YU-LUNG (2015)
A carbon emission tracker is disclosed. The carbon emission tracker includes a main body, a power input interface, a power output interface, a power detecting unit, a communication unit, a memory unit, and a processing unit. The power detecting unit is configured to detect an electricity usage of an electrical appliance. The processing unit is configured to aggregate power consumption data over a time period and to store the power consumption data for the time period to the memory unit. The processing unit transmits the power consumption data of the memory unit to a data center through the communication unit. The power consumption data further includes identification data of the electrical appliance.